Anti-fungal Activity of CNP@GO-MOFs through Synergistic Release of Sodium Lignosulphonate - Chinmaya Mahapatra (Nanochemistry Research, 2025)
In this research, we developed a novel one-step method by using the hydrothermal method to prepare a composite material consisting of redox Cerium Oxide Nanoparticles (CNP)-loaded graphene oxide(GO)-based metal-organic frameworks (MOFs). We loaded sodium lignosulfonate (LS) onto the formulated GO-CNPs and investigated the synergistic antifungal activity of LS-loaded GO-CNPs (LS/GO-CNPs) against Microsporum canis, a common fungal strain causing zoophilic dermatophyte. CNP were incorporated into the framework of GO-MOFs to enhance their antifungal properties due to their interchangeable valency states (Ce (III) and Ce (IV)) and production of Reactive Oxygen Species (ROS) to damage fungal cell wall. The structure and morphology of the composite material were characterized, confirming the successful doping of CNP onto the surface of MOFs. The results demonstrated the superior synergistic antifungal effect of the composite material (MOF), and with sustained drug delivery MOF-LS showed the synergistic effect with respect to the zone of inhibition. Supportively the ROS production was observed to be higher in MOF till 40µg concentration compared to MOF-LS demonstrating the redox nature of MOF resulting in antifungal effect. Highlighting its potential as an effective drug delivery system for combating Microsporum canis infections.